2022
DOI: 10.1158/1535-7163.mct-22-0037
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the Translation Initiation Factor eIF4A Enhances Tumor Cell Radiosensitivity

Abstract: A fundamental component of cellular radioresponse is the translational control of gene expression. As a critical regulator of translational control is the eIF4F cap binding complex, we investigated whether eIF4A, the RNA helicase component of eIF4F, can serve as a target for radiosensitization. Knockdown of eIF4A using siRNA reduced translational efficiency, as determined from polysome profiles, and enhanced tumor cell radiosensitivity as determined by clonogenic survival. The increased radiosensitivity was ac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Having gained an understanding of optimal TSAR assay parameters, we forged ahead and evaluated a diverse set of representative rocaglates with varied core functionality. Our panel consisted of rocaglaol, RocA, silvestrol, CR-1-31-B , SDS-1-021 (64, 65), and the clinical candidate Zotatifin ( eFT226 ) ( Figure 1 ). Each compound was tested at a concentration of 10 µ M in A549 cell lysate pre-loaded with AMP-PNP (1 mM) and (AG) 8 RNA or (CU) 8 RNA (1 µ M), totaling four separate experiments with each rocaglate-RNA pair tested in quadruplicate.…”
Section: Resultsmentioning
confidence: 99%
“…Having gained an understanding of optimal TSAR assay parameters, we forged ahead and evaluated a diverse set of representative rocaglates with varied core functionality. Our panel consisted of rocaglaol, RocA, silvestrol, CR-1-31-B , SDS-1-021 (64, 65), and the clinical candidate Zotatifin ( eFT226 ) ( Figure 1 ). Each compound was tested at a concentration of 10 µ M in A549 cell lysate pre-loaded with AMP-PNP (1 mM) and (AG) 8 RNA or (CU) 8 RNA (1 µ M), totaling four separate experiments with each rocaglate-RNA pair tested in quadruplicate.…”
Section: Resultsmentioning
confidence: 99%
“…Only the vehicles and three RRs did not trigger significant DNA damage in either cell type. Nearly all ADRs and one RR (SDS-1-021 [61][62][63][64][65] , represented twice in the set as both racemic (CMLD011880) and enantioenriched (CMLD010508) stocks) triggered significant DNA damage in PBMC alone. Distinctly, two ADRs induced significant DNA damage in both cell types.…”
Section: Resultsmentioning
confidence: 99%
“…Our results highlight the value of eIF4A as a therapeutic target in vivo and offer a strategy to directly inhibit mRNA translation by targeting eIF4A activity. Studies testing other rocaglates have shown that eIF4A inhibition increases the radiosensitivity of tumors ( 69 ) and also improves the response to targeted therapies, including MEK ( 70 ) and CDK4/6 inhibitors ( 71 ).…”
Section: Discussionmentioning
confidence: 99%